O-034 Intraarterial clot localization in patients with acute ischemic stroke affects the venous microperfusion profile. (4th August 2020) - Faizy, T; Kabiri, R; Leipzig, M; Broocks, G; Christensen, S; Flottmann, F; Lansberg, M; Albers, G; Fiehler, J; Wintermark, M; Heit, J
Abstract : Purpose: The quality of cerebral microperfusion (CM) is strongly related to vessel occlusion location and the robustness of arterial intracranial collaterals (IC) in patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO). The venous microcirculation profile (VMP) may more accurately reflect tissue perfusion compared to arterial IC, but it is unclear to what extent the venous CM profile is affected by arterial clot localization. We determined, if the arterial vessel occlusion localizations predict VMP profile in AIS-LVO patients. Materials and Methods: We performed a multicenter retrospective cohort study of consecutive patients who underwent thrombectomy for AIS-LVO treatment. Patient details were obtained from prospectively maintained stroke databases and the electronic medical record. Baseline CT angiography was used to localize vessel occlusion, which was dichotomized into proximal (internal carotid artery and proximal M1) and distal (distal M1 and M2) occlusions. The primary outcome measure was VMP, which was determined on baseline CTA by the cortical vein opacification score (COVES). COVES for the vein of Labbé, sphenoparietal sinus, and superficial middle cerebral vein were scored as: 0, not visible; 1, moderate opacification; and 2, full opacification. Results: 374 patients met inclusion criteria. 196 patients (52%) had a proximal occlusion and 178 patients (48%) had a distal occlusion. Median COVES was 1 (range 0–5) for proximal occlusion and 3 (range 0–6) for distal occlusion patients. Mann-Whitney-U tests indicated a significant difference between proximal and distal occlusions (p<0.001). Ordinal logistic regression showed that patients with more distal vs proximal occlusions had increased odds of having higher COVES (OR=12.62, [95% CI 8.02- 20.22]; p<0.001), independent of age or presentation NIHSS. Conclusion: The distinct arterial clot localization in AIS-LVO patients affects the cortical venous microperfusion profile. Venous microperfusion was found to be impaired in patients with proximal versus distal vessel occlusions. Disclosures: T. Faizy: None. R. Kabiri: None. M. Leipzig: None. G. Broocks: None. S. Christensen: None. F. Flottmann: None. M. Lansberg: None. G. Albers: None. J. Fiehler: None. M. Wintermark: None. J. Heit: None.